Reduce the Foreign Accent of Indonesian Arabic Learners Through A Minimal Pairs Strategy - Baso, Yusring Sanusi (Arabiyatuna: Jurnal Bahasa Arab, 2022)
The purpose of this study is to discuss how to use the minimal pairs strategy to help students improve their pronunciation abilities. The Research and Development (R&D) and the Quasy Experimental Non-Equivalent Control Group Designs were combined in this study (QENECGD). The R & D method was used to develop a model for implementing the minimal pairs strategy. The QENECGD method was used to evaluate students' final performance following the implementation of the minimal pairs strategy. The study enrolled 50 students who took Basic Arabic Language Proficiency course. Twenty-five students were assigned to the minimal pairs strategy, while the remaining twenty-five served as the control class. All students were required to read an Arabic script during the pre-test and post-tests. The results of these readings were analyzed for pronunciation accuracy using the provided reading script. The Bogaert scale was used in conjunction with the non-parametric test. The findings indicated that the minimal pairs strategy affected students' attainment of a foreign accent level. Additionally, statistical analysis enables the experimental and control groups to be distinguished. Furthermore, the N Gain Score statistic demonstrates the effectiveness of the minimal pairs method.